2020
DOI: 10.1111/jon.12688
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI Predicts Worsening Multiple Sclerosis Disability over 5 Years in the SUMMIT Study

Abstract: BACKGROUND AND PURPOSE Brain MRI‐derived lesions and atrophy are related to multiple sclerosis (MS) disability. In the Serially Unified Multicenter MS Investigation (SUMMIT), from Brigham and Women's Hospital (BWH) and University of California, San Francisco (UCSF), we assessed whether MRI methodologic heterogeneity may limit the ability to pool multisite data sets to assess 5‐year clinical‐MRI associations. METHODS Patients with relapsing‐remitting (RR) MS (n = 100 from each site) underwent baseline brain MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Cognitive batteries are usually complex and time consuming 11 . Similarly, imaging markers of axonal loss that use non-conventional sequences require expertise for their interpretation, which is not always available in most treatment centers 12,13 . The corpus callosum is the largest axonal interhemispheric brain connection.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive batteries are usually complex and time consuming 11 . Similarly, imaging markers of axonal loss that use non-conventional sequences require expertise for their interpretation, which is not always available in most treatment centers 12,13 . The corpus callosum is the largest axonal interhemispheric brain connection.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines how our result can help physicians in selecting those patients that can benefit from an early and more efficacy therapy. A recent study by Bakshi and colleagues found that baseline brain parenchymal fraction, but not T2LL, may be a good predictor of 5-year disability worsening [ 35 ]. A possible explanation to this discrepancy could be researched in the different clinical endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…33 Last, baseline whole-brain volume was the only predictor of disability progression in a recent study from the Serially Unified Multicenter MS Investigation consortium. 34 Because it was shown that the rate of brain atrophy is slower in patients with MS with benign disease 35 and to avoid a potential bias within the 3 disability status groups, we calculated the proportion of patients with benign MS according to the definition based on EDSS and disease duration (EDSS #3.0 and disease duration $15 years). 29 Surprisingly, we found that the disability progression group had a larger proportion of patients with MS with benign disease at baseline (18.7%) compared with 7.9% of patients with MS with benign disease in the disability improvement and 15.2% in the stable groups, respectively.…”
Section: Discussionmentioning
confidence: 99%